The Shadow Pandemic: Examining the Impact of COVID-19 on Zimbabwean Informal Sector in Chiredzi District - Mutizwa, Bismark (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2021)
COVID-19 has disrupted the business sector globally, ushering developed and developing economies into an unprecedented recession beyond anything experienced in nearly a century. Governments across the globe have adopted a myriad of preventive measures. These remedial actions vary from one country to the other. Nonetheless, in Zimbabwe the government gave a blind eye on the informal sector as evidenced by the adopted preventive measures which neglected the plight of informal traders. To this end, this research interrogates the shadow pandemic in the Zimbabwean informal sector using Chiredzi District as an illustrative case study. Documentary review and key informed interviews were at the core of research methodology. The study found out that informal economy businesses are excluded from government grants, closure of businesses, failure to pay rentals, disruption of the supply chain, psychological impact and family dysfunctional are the quandaries causing a shadow pandemic. Inclusion of informal economy businesses in policies and government grants, government should negotiate with landlords, informal traders should be allowed to operate and inclusive social nets are the possible remedial actions that the government can adopted.